A New Approach to Retrieve the Structured Data from a Big Data Set using R - Ray, Sumanta (International Journal of Computer Sciences and Engineering, 2025)
The present research paper computes a step-by-step approach to retrieve the requisite data from big data set, which is heterogeneous in nature. This is done by using R language. Also the process of cleaning, updating, sorting and merging dataset is been explained in this paper. We feel that the comprehensive idea of this research work will be helpful for the researchers, working in the area of big data analysis. Our main goal is to understand the R packages and commands used to analyze big data